Study of Dark Matter with Directionality Approach Using ZnWO4 Crystal Scintillators. (2022) - Leoncini, A.; Afanasieva, L. A.; Belli, P.; Bernabei, R.; Borovlev, Yu. A.; Cappella, F.
No abstract available